Embodied Comprehension: Treatment of Psychosomatic Disorders in Bioenergetic Analysis - Clauer, Jörg (Bioenergetic Analysis, 2022)
Bioenergetic Analysis should prove to be the method of choice in the treatment of psychosomatic diseases. Patients with psychosomatic dissociation need an embodied dialogue with the parent-body of the therapist, i.e. non-verbal somatosensory awareness and attachment as well as verbal dialogue. For the basic construction of a new embodied self the three Ss are needed: Slowness, Safety and Support. In this way the process of therapy supports bodily self-awareness and agency, and a change in the implicit relational knowledge of patient and therapist is co-created. Inevitably, the therapist shares the dissociation of the patient and attunement is disrupted again. By acknowledging his »faults« the therapist regains his self-regulation and is thus available for the regulation of the patient’s somatosensory states and emotions. The new implicit knowledge leads to changes in the »mental organizing principles«. This is shown by an extended case history of ulcerative colitis. Finally exercises and techniques helpful in the work with psychosomatic as well as traumatized patients are described. In this context triangulation is a useful concept.